A Phase 3 Randomized, Double-blind, Multi-center Study to Compare the Safety and Efficacy of IV to Oral Omadacycline to Moxifloxacin for the Treatment of Adult Subjects with CABP (The OPTIC Study). (4th October 2017) - Stets, Roman; Popescu, Monica; Gonong, Joven; Mitha, Ismail; Nseir, William; Madej, Andrzej; Kirsch, Courtney; Das, Anita; Garrity-Ryan, Lynne; Steenbergen, Judith N; Manley, Amy; Eckburg, Paul; et al.
Abstract: Background: Omadacycline (OMC), a novel aminomethylcycline antibiotic, has demonstrated non-inferiority to linezolid for the treatment of acute bacterial skin and skin structure infections. Here we report the results of Omadacycline for Pneumonia Treatment In the Community (OPTIC) Study, a phase 3 study in adults with community-acquired bacterial pneumonia (CABP). Methods: The OPTIC was a randomized (1:1), double-blind, global study comparing OMC and moxifloxacin (MOX) for the treatment of adults with CABP (PORT Risk class II [≤15% total enrollment], III, or IV). Subjects could have received a single dose of a short-acting antibiotic within the 72 hours prior to the first dose of study drug (≤25% total enrollment). Subjects started treatment with OMC 100 mg IV q12h x 2 doses then 100 mg IV q24h, or MOX 400 mg IV q24h. After a minimum of 3 days IV therapy they could switch to oral therapy (OMC 300 mg q24h or MOX 400 mg q12h); total treatment duration was 7–14 days. Early Clinical Response (ECR; 72–120 hours after first dose) was defined as survival, no receipt of rescue antibacterial therapy and improvement in at least 2 of 4 subject symptoms (cough, sputum production, pleuritic chest pain, dyspnea) without deterioration in any of these 4 symptoms. Investigator's Assessment of Clinical Response (Post Therapy Evaluation [PTE] 5–10 days after last dose), was defined as survival with resolution of signs and symptoms of the infection to the extent that further antibacterial therapy was not necessary. A total of 774 subjects were randomized (intent to treat [ITT]. population, N = 386 OMC, N = 388 MOX). Results: Median age was 62.0 years and 20.4% were >75 years. 28.0% of subjects were PORT IV. Efficacy results for OMC vs. MOX were: ECR 81.1% vs. 82.7% [risk difference (RD) -1.6; 95% confidence interval (CI): –7.1, 3.8]; clinical success at PTE 87.6% vs. 85.1% [RD 2.5; 95% CI: –2.4, 7.4]. In the clinically evaluable population ( N = 340 OMC, N = 345 MOX) the clinical success at PTE was 92.9% vs. 90.4%, [RD 2.5; 95% CI: –1.7, 6.8]. Treatment-emergent adverse events (TEAEs) were reported in 41.1% vs. 48.5%; serious TEAEs in 6.0% vs. 6.7% and study drug discontinuation due to TEAE in 5.5% vs. 7.0% of OMC and MOX treated subjects, respectively. Conclusion: OMC was non-inferior to MOX in the treatment of adults with CABP and was safe and well tolerated. Disclosures: C. Kirsch, Paratek Pharmaceuticals: Employee and Shareholder, Salary; A. Das, Paratek Pharmaceuticals: Employee and Shareholder, Salary; L. Garrity-Ryan, Paratek Pharmaceuticals: Employee and Shareholder, Salary; J. N. Steenbergen, Paratek Pharmaceuticals: Employee and Shareholder, Salary; A. Manley, Paratek Pharmaceuticals: Employee and Shareholder, Salary; P. Eckburg, Paratek Pharmaceuticals: Employee and Shareholder, Salary; S. Villano, Paratek Pharmaceuticals: Employee and Shareholder, Salary; E. Tzanis, Paratek Pharmaceuticals: Employee and Shareholder, Salary; P. McGovern, Paratek Pharmaceuticals: Employee and Shareholder, Salary; E. Loh, Paratek Pharmaceuticals: Board Member, Employee and Shareholder, Salary